Uganda : 2002 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2003)
This 2002 Article IV Consultation highlights that since the conclusion of the last Article IV consultation in March 2001, Uganda has continued to implement disciplined financial policies and sound structural reforms that have helped to sustain robust economic growth despite an adverse external environment. In 2001/02 (July-June), real GDP growth increased to 6.6 percent, boosted by highly favorable weather conditions for agriculture and a surge in construction activity from a pickup in investment. A sharp drop in food crop prices resulted in negative headline inflation of -2.5 percent during the year.